Non-vitamin K-dependent oral anticoagulants have a positive impact on ischaemic stroke severity in patients with atrial fibrillation - Hellwig, Simon (Europace, 2018)
AIMS: Several studies showed reduced stroke severity in patients with atrial fibrillation (AF) if the international normalized ratio (INR) was ≥ 2 at stroke onset. There are no respective data for non-vitamin K-dependent oral anticoagulants (NOACs). The aim of this study was to compare the impact of NOAC or phenprocoumon intake on stroke severity. METHODS AND RESULTS: In this single-centre observational study, 3669 patients with acute ischaemic stroke were retrospectively analysed regarding AF status and medication immediately before admission. Using multivariable regression, we analysed the association of pre-admission anticoagulation with severe stroke (National Institutes of Health Stroke Scale score ≥ 11) on admission and poor outcome at discharge (modified Rankin scale score > 2). Before the index stroke, 655 patients had known AF and a CHA(2)DS(2)-VASc score ≥ 2. While 325 (49.6%) patients were anticoagulated, 159 (24.3%) were prescribed a NOAC and 75 (11.5%) phenprocoumon patients had an INR ≥ 2 on admission. Compared with AF patients without medical stroke prevention, an INR ≥ 2 [OR 0.23 (95% CI 0.10–0.53)] or NOAC intake [OR 0.48 (95% CI 0.27–0.86)] were associated with a lower probability of severe stroke after adjustment for confounders, while an INR < 2 [OR 0.62 (95% CI 0.33–1.16)] was not. Adjusted odds ratios for poor functional outcome at hospital discharge were 0.47 (95% CI 0.27–0.84) for NOAC patients, 0.33 (95% CI 0.17–0.65) for INR ≥ 2 and 0.61 (95% CI 0.32–1.16) for INR < 2. CONCLUSION: NOAC intake before stroke did reduce the probability of severe stroke on hospital admission and poor functional outcome at hospital discharge as similarly demonstrated for phenprocoumon patients with an INR ≥ 2 on admission.